CAREER – LIFE-LONG SELF-IMPROVEMENT PROCESS - Marta Matulcikova; Daniela Brevenikova (European Scientific Journal, ESJ, 2014)
The paper deals with career as a life-long process which leads to an individual’s self-improvement. The aim of the paper is to characterise career on the basis of selected opinions of domestic and foreign authors of the process of career implementation, which represents a particular career path chosen by an individual or which is a matter of random influences. We approach to the concept of career in the context of factors operating at individual stages of career as well as in various periods of human life. We indicate features of career development, types of career and approaches to the issue of career path. In a separate chapter, we pay attention to job mobility as part of career development and to concepts which denote various kinds of movement of career (promotion, relocation and leaving a workplace). The paper is a partial result of the second stage of the research carried out under the research project KEGA 006EU-4/2013 – “Methods and principles applied in the preparation of structure and content of the subject disciplines supporting the development of economics knowledge and business skills in students of non-economic study programmes of the second cycle of higher education”. The starting-point of philosophy of our research is an assumption of the role of education in an employee’s career. In the empirical part of the paper, we summarise findings resulting from the questionnaire research. The output of research carried out so far is the model of career in terms of career movements in this paper.